Effects of strength training on the treatment of patellofemoral pain syndrome - a meta-analysis of randomized controlled trials - Rodrigo Kohn Cardoso; Eduardo Lucia Caputo; Airton José Rombaldi; Fabrício Boscolo Del Vecchio
Abstract Introduction: Palletofemoral pain syndrome (PFPS) is anterior knee pain that affects around 25% of the population at some point in their lives. Muscle weakness is one of the main causal factors related to PFPS. Objective: Conduct a quantitative analysis on the effectiveness of strength training at reducing pain in PFPS sufferers. Methods: An electronic search was conducted on the MEDLINE, Pubmed, EMBASE, Lilacs and Scielo databases for studies published between January 2005 and September 2014. The following descriptors were used: "patellofemoral pain syndrome", "patellofemoral pain", "retropatellar pain", "exercise", "exercise therapy", "strength", "rehabilitation". Only randomized controlled trials (RCTs) that compared the effects of strength training to no exercise in terms of reducing pain among PFPS sufferers were included. Data were extracted by two independent authors using predefined quality indicators. Results: A total of 39 RCTs were initially identified in the search. However, only five met the inclusion criteria. Strength training exhibited a positive effect on PFPS (SMD = 0.85, CI: 0.45-1.25). However, high heterogeneity was observed between the studies (p < 0.05; I 2 = 68.3%). Conclusion: Strength training showed a statistically positive response in the treatment of PFPS.